STAT3/LKB1 controls metastatic prostate cancer by regulating mTORC1/CREB pathway - Pencik, Jan; Philippe, Cecile; Schlederer, Michaela; Atas, Emine; Pecoraro, Matteo; Grund-Gröschke, Sandra; Li, Wen Jess; Tracz, Amanda; Heidegger, Isabel; Lagger, Sabine; Trachtová, Karolína; Oberhuber, Monika; et al. (Molecular cancer, 2023)
Prostate cancer (PCa) is a common and fatal type of cancer in men. Metastatic PCa (mPCa) is a major factor contributing to its lethality, although the mechanisms remain poorly understood. PTEN is one of the most frequently deleted genes in mPCa. Here we show a frequent genomic co-deletion of PTEN and STAT3 in liquid biopsies of patients with mPCa. Loss of Stat3 in a Pten-null mouse prostate model leads to a reduction of LKB1/pAMPK with simultaneous activation of mTOR/CREB, resulting in metastatic disease. However, constitutive activation of Stat3 led to high LKB1/pAMPK levels and suppressed mTORC1/CREB pathway, preventing mPCa development. Metformin, one of the most widely prescribed therapeutics against type 2 diabetes, inhibits mTORC1 in liver and requires LKB1 to mediate glucose homeostasis. We find that metformin treatment of STAT3/AR-expressing PCa xenografts resulted in significantly reduced tumor growth accompanied by diminished mTORC1/CREB, AR and PSA levels. PCa xenografts with deletion of STAT3/AR nearly completely abrogated mTORC1/CREB inhibition mediated by metformin. Moreover, metformin treatment of PCa patients with high Gleason grade and type 2 diabetes resulted in undetectable mTORC1 levels and upregulated STAT3 expression. Furthermore, PCa patients with high CREB expression have worse clinical outcomes and a significantly increased risk of PCa relapse and metastatic recurrence. In summary, we have shown that STAT3 controls mPCa via LKB1/pAMPK/mTORC1/CREB signaling, which we have identified as a promising novel downstream target for the treatment of lethal mPCa.
Keywords: AMP-Activated Protein Kinases; Diabetes Mellitus, Type 2; zvířata; Male; metformin; STAT3 Transcription Factor; Metformin; Mice; mTORC1; Animals; proteinkinasy aktivované AMP; mužské pohlaví; diabetes mellitus 2. typu; lokální recidiva nádoru; transkripční faktor STAT3; Mechanistic Target of Rapamycin Complex 1; lidé; nádory prostaty; Humans; Neoplasm Recurrence, Local; Prostatic Neoplasms; myši